Answer:
Explanation:
f(g(x)) means substituting g(x) in f(x)
ie, 3(2x-3)+1 = 6x-9+1 = 6x - 8
g(f(x)) means substituting f(x) in g(x)
ie, 2(3x+1)-3 = 6x2-3 = 6x - 1
f(x} = 3x + 1
g(x} = 2x -- 3
f(g(x)) = 3x + 1. (Calm down right?)
Let the x in the expression be (2x -- 3)
N.B x = g{x}
f(g(x)) = 3(2x --3} + 1
Open bracket
f(g(x)) = 6x -- 9 + 1
f(g(x)) = 6x -- 8...
2... Solve for g(f(x)), using the same strategy
g(f(x)) = 2x -- 3
x = f(x)
g(f(x)) = 2(3x + 1) -- 3
g(f(x)) = 6x + 2 -- 3
g(f(x)) = 6x -- 1
#AllonGod
5.3m questions
6.9m answers